Cytoplasmic HMGB1 promotes and interacts with BECN1 through ZNF460 to induce autophagy and accelerate radioresistance in colorectal cancer cells - Han, Yuhui; Liu, Xiuxin; Sheng, Wenjiong; Kuang, Ruixue; Zhang, Yan; Jia, Xinyu; Abd El-Aty, A. M.; Hu, Tao; Wang, Bin; Ma, Yanchao (Frontiers in Immunology, 2025)
Radioresistance results in relapse and treatment failure in locally advanced colorectal cancer (CRC) patients. HMGB1 is reportedly associated with radioresistance in esophageal squamous cell carcinoma and breast cancer. However, its role in the response of CRC to radiotherapy has not been fully elucidated. Thus, we explored the role and underlying mechanism of HMGB1 in CRC radioresistance. The total amount of HMGB1 and its translocation from the nucleus to the cytoplasm increased after irradiation. Functional studies revealed that HMGB1 enhanced the proliferation and autophagy of CRC cells after irradiation. Mechanistically, HMGB1 can regulate the transcription factor ZNF460, which combines with the BECN1 promoter to promote the release of BECN1 into the cytoplasm after irradiation. Moreover, HMGB1 directly interacts with BECN1 in the cytoplasm, thereby resulting in CRC radioresistance. Finally, the protein expression levels of BECN1, which was positively correlated with HMGB1, were significantly increased in human CRC tissues and associated with TNM stage and poor prognosis in patients with CRC. Our findings revealed that HMGB1 plays a vital role in CRC radioresistance by regulating autophagy through binding with BECN1. Given the efficacy of HMGB1 modulation in CRC suppression and radioresistance, HMGB1 has emerged as a potential therapeutic molecule for CRC treatment.